Pengaruh Model Pembelajaran SAVI (Somantik, Auditori, Visual Dan Intelektual) Terhadap Kemampuan Menulis Karangan Argumentasi Siswa SMA - Saraswati Saraswati; Nanang Maulana (Universitas Mathla'ul Anwar Banten, 2019)
This research is motivated by the low writing skill of students' argumentative essay causing low student learning outcomes. The method used in this study is the experimental method conducted at SMAN 17 Pandeglang by taking class X students in the 2015/2016 academic year as a population. The sample technique used is cluster random sampling. The draw results conducted on the five existing classes were obtained, namely the X-IPS 1 class as the experimental class and X-IPS 3 class as the control class. Each class is 25 and 24 students. Thus the number of samples in this study were 49 students. The experimental class is given treatment, namely the learning process using the SAVI model (Somantik, Auditory, Visual and Intellectual). Whereas the control class uses the expository model. Based on the results of data analysis in statistical calculations, it can be concluded that there is a positive effect of SAVI learning model at student writing skill of argumentative essay at class X, SMAN 17 Pandeglang 2015/2016 academic year. This is indicated by data from the analysis using the t-test formula, obtained t-count 2.984. Whereas t-table for the significance level of 0.05 with degrees of freedom (df) 47 obtained t-table 2.014. Because t-count is greater than t-table (t-count> t-table), which is 2.984> 2.014, then the null hypothesis (Ho) is rejected. By rejecting of the null hypothesis (Ho), then the alternative hypothesis (Ha) is accepted. Thus, it means that there is significant effect of using SAVI learning model at student writing skill of argumentative essay.